2017
DOI: 10.3390/su9071152
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Ukrainian Forests to Climate Change

Abstract: Abstract:Ukraine is a country of the Mid-Latitude ecotone-a transition zone between forest zone and forestless dry lands. Availability of water defines distribution of the country's forests and decreases their productivity towards the south. Climate change generates a particular threat for Ukrainian forests and stability of agroforestry landscapes. This paper considers the impacts of expected climate change on vulnerability of Ukrainian forests using ensembles of global and regional climatic models (RCM) based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 34 publications
2
44
0
14
Order By: Relevance
“…This area is located in the mountain conditions of Carpathians, on a steep slope at 1280 m a.s.l. We also did not consider pine forests located in bioclimatic zones of southern forest steppe and steppe, because these territories belong to a xeric belt (an ecotone between the forest zone and southern forestless dry lands) where pine forests are forecasted as a tipping element due to the critical water stress there (Shvidenko et al 2017).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This area is located in the mountain conditions of Carpathians, on a steep slope at 1280 m a.s.l. We also did not consider pine forests located in bioclimatic zones of southern forest steppe and steppe, because these territories belong to a xeric belt (an ecotone between the forest zone and southern forestless dry lands) where pine forests are forecasted as a tipping element due to the critical water stress there (Shvidenko et al 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Several studies have predicted that the growth of Scots pine and Norway spruce will increase by climate change due to improved climatic conditions and accelerated nutrient cycling, particularly in the boreal and temperate regions where a water stress is not expected (Lindner et al 2010, Hlasny et al 2011. The risk for severe drought periods is, however, projected to increase especially in the southernmost areas of the distribution of these tree species, out of the study area (Babst et al 2013, Zang et al 2014, Shvidenko et al 2017, adding uncertainty to the predictions. Increased drought may also increase the risk of fires and insect outbreaks as these stands get more stressed.…”
Section: Climate Change Impactsmentioning
confidence: 99%
“…International efforts to mitigate global climate change demonstrate both evident progress and significant challenges to overcome due to the complexities of carbon cycle regulation worldwide, as well as substantial uncertainties in the mechanisms of its estimation [5]. The forests of Ukraine, covering nearly 16% of the country's land area and providing a substantial carbon sink [6], have recently undergone changes and are very likely to face high climate, hydrology, and management-induced risks in the future [7]. Ukraine's forests are situated in the mid-latitude ecotone, that is, in a transition area between the zone of temperate forests and forestless steppe: e.g., according to the abovementioned study [7], under certain climatic scenarios, a substantial worsening of growth conditions in Ukraine is forecasted by the end of this century mainly due to the water stress.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary spruce stands are vulnerable to many challenges today (Schutz et al 2006), with climate change being chief among them . Recently, some studies have shown that spruce stand dominance will decline in the Ukrainian Carpathians over the next 500 years due to climate change (Hlásny et al 2016, Shvidenko et al 2017, Kruhlov et al 2018. A sharp increase in the number of cumulative dry days, a significant decrease of precipitation during a growing season, and a higher frequency of extreme events (drought, windstorms, abundant rainfall within short periods of time) are regarded as the most detrimental factors facing Norway spruce.…”
Section: Introductionmentioning
confidence: 99%